The prevalence of asthma-COPD overlap (ACO) among COPD patients and the role of prostaglandin D2 (PGD2) in differential diagnosis “about” - Atlı, Siahmet (Pamukkale University, 2026)
[No abstract available]
KOAH hastaları arasında astım-KOAH overlap (AKO) sıklığı ve ayırıcı tanıda prostaglandin D2 (PGD2)' nin rolü "hakkında"
Keywords: Biological Marker; Bronchodilating Agent; Prostaglandin D2 Derivative; Asthma; Chronic Obstructive Lung Disease; Classification; Differential Diagnosis; Forced Expiratory Volume; Human; Inflammation; Letter; Phenotype; Prevalence